3D printed silicone platforms with laser-scattering protein detection under flow analysis conditions as a development of Silicone Optical Technology (SOT) - STRZELAK, Kamil; MALASUK, Chacriya; OKI, Yuji; MORITA, Kinichi; ISHIMATSU, Ryoichi (Microchemical journal, 2020)
•Designs of 3D printed silicone analytical platforms for total protein determination have been presented.•This research is a development of recently presented idea of silicone optical technology (SOT) as a next step to fabricate all-in-one 3D printed analytical devices.•The optimized microfluidic system is sufficient for total protein analysis with limit of detection of 3 mg/L and linearity range of 16 – 400 mg/L.•The analytical usefulness of developed microfluidic system has been proved by the determination of total protein in urine samples. In this work, the 3D printed silicone microfluidic systems with simultaneous laser-scattering detection for turbidimetric and nephelometric measurements are presented. As a model reaction, the Exton method for total protein determination has been chosen as the well-known analytical protocol. Presented research is a development of recently presented idea of Silicone Optical Technology (SOT). It can be considered as the next step for all-in-one 3D printed analytical system concept, which means that microfluidic platform as well as detection system parts can be constructed during one-step manufacturing process. During the investigations, three microfluidic platforms with different flow-mixing patterns were designed and optimized for flow rate and sample injection volume. The most promising system with so-called 3D mixing (mixing channel along three axes) was characterized by analytical parameters sufficient for total protein analysis: limit of detection of 3 mg/L, linearity in the range of 16 – 400 mg/L and 50 µL sample consumption. The analytical usefulness of developed microfluidic platform was proved by analysis of urine samples. Furthermore, the design and setting up of double detection system based on Arduino microcontroller have been discussed. [Display omitted]